Novel Modified Algorithm for High Fat/High Energy Density Meal in Type 1 Diabetes: Less Hypoglycemia - Yasemin Atik Altınok; Günay Demir; Hafize Çetin; Samim Özen; Şükran Darcan; Damla Gökşen (Galenos Yayincilik, 2023)
INTRODUCTION: This aim of this study was to investigate the effect of additional insulin dosing for high fat/high energy density mixed meal over 12 hours. METHODS: In this single-center, non-blinded, randomized, cross-over study, a high fat/high energy density test meal was used to study the impact on glycemic response of either carbohydrate counting (CC) on the first day and the Pańkowska algorithm (PA) on the second test day. The two methods were compared in 20 adolescents with type 1 diabetes (T1D), aged 9-18 years, using insulin pump therapy and continuous glucose monitoring on postprandial early (0-120 min), late (120-720 min), and total (0-720 min) glycemic response. RESULTS: There was no difference between groups in the duration of normoglycemia in the early period. Postprandially, 50% of patients developed hypoglycemia using the PA at a median of 6.3 (5.6-7.9) hours and the PA was subsequently modified for the remaining ten patients. Area under the curve (AUC) for the early period decreased non-significantly in the CC group, indicating less normoglycemia. No significant difference was found in the AUC of the PA (no hypoglycemia n=4) and modified PA groups (no hypoglycemia n=6) over the whole period (0-12 hours). AUC for level 2 hyperglycemia was statistically greater in the PA-no hypoglycemia patients compared to modified PA-no hypoglycemia patients. DISCUSSION AND CONCLUSION: There were inter-individual differences in glycemic response to high fat/high energy density meals. An individualized approach to insulin dosing by evaluating food diary and postprandial glucose monitoring appears to be optimal for children and adolescents with T1D.